TREND REFORMASI PENDIDIKAN DI AUSTRALIA - Esha, Muhammad In’am (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Change is an important term in this era. Change is a phenomenon that able to seen in various aspects such as politic, economic, social, and education. Political reform or education reform that make a trend in the world, actually speak about change. This paper examines education reform in Australia. This study shows several aspect on that phenomenon. First, education reform in Australia influenced by spreading of neoliberalism trend in the world with a famous term: new public management paradigm. As member of OECD, Australia must develop and modernize its education as well as in New Zealand, England, Japan, and USA. Second, education reform needed for competing in globalization era. Relation of education with increasing human resources is an important factor that encourage education reform. Third, education reform in Australia include two aspect: managerial aspect and content of education (curriculum). Keyword: Reform, Education, New Public Management.